Ethical management of Gold mine workers with early and mild silicosis in South Africa - Mojakwana, Angeline (My University, 2024)
The South African Gold Mining industry is an inherently risky working environment, with frequent accidents and crystalline silica dust exposure that causes silicosis and other cardiorespiratory and autoimmune complications. These diseases can considerably impact the gold mining industry and potentially lead to public health disasters by exacerbating existing tuberculosis (TB) burden in communities and the public health sector. It is of utmost importance to control silica dust exposure and to protect mineworkers from the impact of silicosis. In this study, I interrogate the morality of issuing certificates of fitness to already affected mineworkers to continue risk work underground where they are further exposed to silica dust, which leads to accelerated progression of their illness and its complications. Specifically, the study defends the thesis statement that mineworkers with early and mild silicosis ought not to be certified to continue risk work underground in the gold mining environment where they are further exposed to silica dust. A normative principle derived from the combination of key principles in welfarism and Afro -communitarian solidarity was used to defend the claim. This mostly evaluative study – that draws on desktop-based research – outlines many recommendations, including a revision of Occupational Diseases of Mines and Works Act ODMWA (given that the Act is insufficient and not adequately inclusive), continuous evaluation, monitoring and improvement of control processes to mitigate the impact of silica dust exposure and silicosis and alternative reasonable accommodation of mineworkers with silicosis to protect them from further exposure to silica dust.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, University of the Witwatersrand, School of Anatomical Sciences, Johannesburg, 2023
Keywords: Ethical management; Gold mines; Mild silicosis; South Africa; SDG-3: Good health and well-being